ウジョウ ケイソウ NAVICULA GIBBULA VAR PERAUSTRALIS ノ ヘンイ - 小林, 艶子; コバヤシ, ツヤコ; KO-BAYASHI, Tsuyako (国立極地研究所, 1965)
P(論文) Navicula gibbula var psraustralis was found in the materials collected by Dr. Hiroshi FUKUSHIMA, assistant professor of Yokohama Municipal University, at Shinnan Rocks on the Prince Olav Coast of Antarctica in 1961 and by Mr. David T. MASON of California University at Cape Barne of Ross Island. The writer, after cleaning the specimens with acid and mounting them with pleurax on slides, took microphotographs at random and enlarged them 2,000 times as large. Then the writer investigated 117 leaves of the former material and 68 leaves of the latter meterial. In external shape structure, and measured values of the shell, this diatom resembles Navicula gibbula CLEVE, except that both margins are protruded and ends are sometimes expanded in a capitate shape. However, individuals in distinguishable from Navicula gibbula are also found though rarely. They are similar to Navicula bachmanii HUST. in the point that both ends were expanded in a capitate shape, but expansion of the central part of the shell is quite different and the number of striae in 10μ is also different. This diatom closely resembles the new species (Navicula peraustralis) collected by J. MURRAY during the British Antarctic Expedition, 1907 to 1909, from the recent geological deposit containing subfossil diatoms at Cape Royds near Cape Barne, one of the stations the writer investigated this time, but the structure of striae was a little different from the original drawing of WEST. As the writer pointed out in the previous paper, in consideration of inaccurate drawing or incomplete observation on Navicula muticopsis, Pinnularia cymatopleura and Tropidoneis laevissima in WEST'S paper, it would be better to identify the diatom which was found this time as Navicula peraustralis. Judging from the characteristics of the shell as mentioned before, it would be better to regard this diatom not as a species but as a variety of Navicula gibbula CLEVE. Thus the writer proposes the following name : Navicula gibbula CLEVE var. peraustralis (W. & G. S. ...